Assessment of the effectiveness of the reforms to support entrepreneurship in Uzbekistan - Tadjiev Bekhzod Umidjanovich; Ataev Jasur Erkinovich; Akhmetshin Elvir Munirovich; Vasilev Vladimir Lvovich; Kukhar Viktor Stanislavovich (E3S Web of Conferences, 2023)
The relevance of the present research is conditioned by the increased role of small business in the rapidly changing world. Providing a significant contribution to the country’s gross domestic product and employment indicators, small business is highly flexible and adaptive to changes. World experience shows that a government is able to increase the multiplier effect of private entrepreneurship in the country through a system of measures and strategic programs aimed at its support and development. Such actions of the government should take into account the peculiarities of the territory and unique national advantages. This paper considers the effectiveness of reforms implemented to create a favorable environment for business entities of different levels in Uzbekistan, including small business and private entrepreneurship, based on various economic mechanisms. The study assesses the impact of reforms implemented in different periods on the activity rate and survival rate of business entities. These indicators were calculated on the basis of official statistical information. The methods of mathematical statistics were used to calculate these indicators. The results were evaluated using the methods of comparative and system analysis. In addition, changes in the activity rate and survival rate of small businesses due to economic fluctuations caused by the coronavirus pandemic were investigated.